Drivers of Skilled Workforce Migration from Nepal - Gautam, Tara Prasad; Adhikari, Babu Ram (State, Society and Development: PMPD Perspectives, 2025)
This paper assesses the drivers of skilled workforce migration from Nepal between 2000 and 2025, synthesizing insights from 50 peer-reviewed studies, policy documents, and labor migration data. Using a systematic review method, identifies three primary drivers: economic factors, political and social instability, and socio-cultural influences. Skilled professionals—particularly in healthcare, education, and IT—are pushed abroad by low wages, limited career growth, centralized governance, and politicized institutions. Pull factors such as higher salaries, professional recognition, and improved working conditions in countries like South Korea, Japan, Germany, and the UK have further accelerated this trend. Gendered patterns are increasingly evident, with rising female migration in the nursing sector driven by both opportunity and domestic structural inequities. Despite remittances contributing over 25% to Nepal’s GDP, labor migration remains overwhelmingly dominated by unskilled and low-skilled workers; about 74% of those receiving labor permits are categorized as “unskilled.” However, the gradual rise in skilled and semi-skilled outmigration—particularly in healthcare, engineering, and IT—is beginning to impact critical domestic sectors, especially in urban and economically active regions. The study emphasizes the need to view skilled professionals not as exportable resources, but as vital agents of national transformation.